2018
DOI: 10.1016/j.seizure.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Generalized seizures presurgically in a cohort of children with hemispherectomy: Predictors and a potential link to surgical outcome?

Abstract: Generalized seizures were not an absolute contraindication for hemispherectomy. Those patients with ESES might experience generalized seizures presurgically. Focal to bilateral tonic-clonic seizures and myoclonic-atonic seizures pre-surgery may indicate unfavourable post-operative seizure outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Our case series includes 14 patients, the largest single center cohort of patients to have undergone resective surgery for ESES. Similar to other reports, most patients received hemispherotomy surgery (10/14) (23,(25)(26)(27)(28)47). The seizure outcomes for the hemispherotomy subgroup are universally excellent with seizure freedom achieved in all patients.…”
Section: Clinical Outcomessupporting
confidence: 81%
“…Our case series includes 14 patients, the largest single center cohort of patients to have undergone resective surgery for ESES. Similar to other reports, most patients received hemispherotomy surgery (10/14) (23,(25)(26)(27)(28)47). The seizure outcomes for the hemispherotomy subgroup are universally excellent with seizure freedom achieved in all patients.…”
Section: Clinical Outcomessupporting
confidence: 81%
“…Abnormalities were extensive, involving all aspects of the frontal lobe (basal-medial-lateral) and extending up to the primary motor-sensory strip and anterior insula. Several series of young pediatric cases, across a variety of substrates, have shown that the presence of an encephalopathic background with "generalized" and "diffuse" interictal and ictal EEG features should not, on its own, be prohibitive for resective surgery, in case a well-defined epileptogenic lesion can be imaged [17][18][19][20][21] especially if, at least some EEG "clues" for a lesion-concordant lateralization exist. 22,23 Given this background knowledge, and despite the absence of clear lateralizing/localizing EEG and semiological features, we opted for a generous frontal lobectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally assumed that a focal semiology (e.g. clonic arm movements contralateral to the affected hemisphere) is another data point that supports pursuing HDS while generalized seizures may portend lower rates of seizure freedom post-hemispherotomy (Carmant et al, 1995;Liu et al, 2018). If the lateralization of seizure onset is still in question after obtaining brain MRI and EEG, then PET, ictal SPECT (SISCOM), and/or MEG/MSI may play a role in lateralizing seizure onset.…”
Section: Discussionmentioning
confidence: 99%